Religious Pluralism and Peace: Lessons from the Medina Charter - Mohamed Bin Ali (2016)
The Medina Charter constituted by Prophet Muhammad in 622 in Arabia was intended to end inter-tribal conflicts and maintain peace and cooperation among the Medinan people 1,400 years ago. Many lessons can be drawn from the Charter to enhance peaceful inter-religious relations today amid current moves to revive this historic document.